Automated grid fault detection and repair - Luyt, Leslie (Rhodes University, Faculty of Science, Department of Computer Science, 2012)
With the rise in interest in the field of grid and cloud computing, it is becoming increasingly necessary for the grid to be easily maintainable. This maintenance of the grid and grid services can be made easier by using an automated system to monitor and repair the grid as necessary. We propose a novel system to perform automated monitoring and repair of grid systems. To the best of our knowledge, no such systems exist. The results show that certain faults can be easily detected and repaired.,TeX,Adobe Acrobat 9.51 Paper Capture Plug-in
Keywords: Computational grids (Computer systems) -- Maintenance and repair; Cloud computing -- Maintenance and repair; Computer architecture